Variation in expression of HMW1 and HMW2 adhesins in invasive nontypeable Haemophilus influenzae isolates - Mastrantonio Paola; Cardines Rita; Carattoli Alessandra; Giufrè Maria; Cerquetti Marina (BMC Microbiology, 2008)
Abstract Background Among surface antigens of nontypeable Haemophilus influenzae (NTHi), the HMW1 and HMW2 proteins are the major adhesins promoting colonization of the upper respiratory tract. Since they are potential vaccine candidates, knowledge concerning variation in HMW proteins expression among clinical isolates is of great interest. In this study, expression of hmw1A and hmw2A genes was evaluated by quantitative real-time reverse transcription-PCR in 3 NTHi invasive isolates (strains 56, 72, 91) and in the prototype strain 12. Number of 7-bp repeats within the hmwA promoters and presence of HMW proteins by Western blotting were also determined. Results Results showed that gene transcription varied not only among different isolates but also between the hmw1A and hmw2A genes from the same isolate. Compared to that found in prototype strain 12, up-regulation of the hmw1A gene expression was found in strain 56, down-regulation of both hmw1A and hmw2A genes transcripts was observed in strain 72 whereas the two hmwA genes appeared differentially expressed in strain 91 with the hmw1A transcript enhanced but the hmw2A transcript reduced. Conclusion Increasing numbers of 7-bp repeats within the hmwA promoters generally correlated with decreased amounts of mRNA transcript, however additional control mechanisms contributing to modulation of hmw1A gene seem to be present.